Nonpharmacological management of dental anxiety in the general population and individuals with learning disabilities: a bibliometric analysis - Ibrahim, Siti Hajar; Mohd, Farah Natashah; Mohd Yusof, Mohd Yusmiaidil Putera; Chandra, Lukman Ade; Ahmi, Aidi; Ahmad, Mas Suryalis (John Wiley & Sons, 2025)
Aims: Dental anxiety (DA) is reported among the general population, including individuals with learning disabilities (LDs). In many studies, nonpharmacological interventions have been applied to significantly improve DA among patients. This study aimed to examine publication trends and patterns in both populations to identify the current research trends and literature gaps. Methods: A descriptive analysis of bibliographic data and network visualization were conducted using Microsoft Excel and VosViewer, focusing on literature published in the Scopus database between 1994 and 2023 and using “title” as the search field. Results: For the study period, the following were identified: 1429 authors, 5858 total citations, and an h-index of 36. From a total of 2058 publications discovered, 363 publications were included in the study. Of these, only 11 articles addressed nonpharmacological management for people with LDs. In terms of the research country, the United Kingdom was the leading contributor, with 56 publications. Ad de Jongh was the most productive author, with 13 publications and 447 citations. The most highly cited paper was Lehrner et al. (2005), with 312 citations. Conclusion: This study determined the number of publications related to nonpharmacological management of DA over three decades. The number of studies involving people with LDs was lower than that involving the general population, suggesting future research should occur in this area.